Neutron Star Matter - Ellis, Dale D. (My University, 1971)
An expression is obtained for the energy per particle in neutron star matter. The energy per particle is expressed as a function of, y, the ratio of protons to the total number of nucleons in the system. Minimizing the energy with respect to y gives the optimum proton ratio at a given density. Using an effective nuclear force, the results were extrapolated to a density of p = 6pNM. The proton ratio is rather sensitive to the force used, but all forces used indicated a peak in the proton concentration at p (approximately equal to) 2pNM. The expression for the energy as a function of y was also used to interpolate the energy per particle between the nuclear matter and neutron . gas limits. The form of this interpolation is important in determining the stability of neutron-rich nuclei.
Keywords: energy per particle, neutron star matter, protons, proton ratio, proton concentration, neutron-rich nuclei